2013
DOI: 10.1027/2151-2604/a000136
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Children’s Choices and Cognition in Video Game Play

Abstract: This article provides a synthesis of a group of research studies conducted to better understand in what ways children’s entertainment video game play choices relate to their creativity, motivations, problem-solving strategies, learning preferences, and beliefs about how to play games. Three studies were conducted among American students: (1) a survey and creativity assessment with students aged 9–11, (2) an in-depth qualitative study with three adolescent boys, and (3) an online survey. Key findings from this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…Similar to Jessica, other participants felt as though the player’s guide and YouTube walkthrough provided the ability to guide the participant in the right direction rather than just giving them the right answer since they still had to complete the task. The present study discovered similar findings to that of previous research (e.g., Hamlen, 2013). Namely, we found that participants utilized outside tools to solve difficult tasks.…”
Section: Findings and Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Similar to Jessica, other participants felt as though the player’s guide and YouTube walkthrough provided the ability to guide the participant in the right direction rather than just giving them the right answer since they still had to complete the task. The present study discovered similar findings to that of previous research (e.g., Hamlen, 2013). Namely, we found that participants utilized outside tools to solve difficult tasks.…”
Section: Findings and Discussionsupporting
confidence: 93%
“…Other studies have found that individual’s desire to play video games is based on recreation as they seek rewards and relaxation associated with video gameplay (Hamlen, 2013; Mentzoni et al, 2011). In addition to experience the enjoyment or escape offered by video games, video games also seem to have an effect on players’ social behaviors, such as empathy and teamwork (Happ et al, 2013; Stenico & Greitemeyer, 2014).…”
Section: Research On Effects Of Video Gameplaymentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of youngsters enjoyed computer games but disliked the boring contents in textbooks [8] . The features of computer games were believed to have shaped students' cognitive abilities of and motivation towards learning, contrasting with monotonous and unattractive scholastic contents in traditional instruction [27] . There was a sharp contrast between formal education and computer games [28] .…”
Section: Literature Reviewmentioning
confidence: 99%